Literasi Guru terhadap Standar Lulusan Tingkat Sekolah Menengah Kejuruan - Nursyaban, Abdul Aris; Ramdani, Muhammad Ali; Rachman, Chaerul; Basri, Hasan (Universitas Islam Sultan Agung, 2022)
This study aims to describe a comparative analysis of the standard literacy understanding of graduates from 15 PAI and 15 Non PAI teachers and to find the legal basis for graduate standards, then pay attention to each indicator. The method used in this research is descriptive quantitative method. As a previous study, no one has analyzed the comparison of literacy understanding standards for PAI and Non PAI teacher graduates as a form of reference from the government. The researchers took 15 samples of PAI teachers and 15 samples of non-PAI teachers. The population in this study were 38 teachers from Bandung City Vocational High School and a sample of 15 PAI teachers and 15 non PAI teachers was selected. Data collection techniques using questionnaires and triangulation interview data analysis. Collecting data and questionnaires using google forms which are distributed to 15 PAI teachers and 15 non PAI teachers. Collect authentic data and triangulate the results of interviews with several teachers which are taken from filling out google forms, from the lowest and highest data, also analyze the results of the comparison between PAI and Non PAI, so 8 respondents PAI is superior and Non PAI 7 respondents are superior to 15 respondents presented by researchers.Â Penelitian ini bertujuan memaparkan analisis perbandingan pemahaman literasi standar lulusan dari 15 guru PAI dan 15 Non PAI dan menemukan dasar hukum standar lulusan, lalu diperhatikan setiap indikator. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif deskriptif. Sebagai penelitian terdahulupun belum ada yang menganalisis perbandingan pemahaman literasi Standar lulusan guru PAI dan Non PAI sebagai bentuk acuan dari pemerintah. Adapun peneliti mengambil 15 sample guru PAI dan 15 sample guru non PAI. Populasi pada penelitian ini adalah 38 orang guru SMK kota Bandung dan dipilih sampel sebanyak 15 orang guru PAI dan 15 orang guru Non PAI. Teknik pengumpulan data menggunakan kuesioner dan analisis data wawancara triangulasi. Pengambilan data dan kuesioner menggunakan google form yang disebar disetiap 15 guru PAI dan 15 guru Non PAI. Mengumpulkan data otentik dan triangulasi hasil wawancara dengan beberapa guru yang mana diambil dari pengisian google form, dari data yang terendah dan tertinggi, juga menganalisis hasil perbandingan antara PAI dan Non PAI, maka 8 responden PAI lebih unggul dan Non PAI 7 responden lebih unggul dari 15 responden yang disajikan oleh peneliti